The Efficacy of Strontium and Potassium Toothpastes in Treating Dentine Hypersensitivity: A Systematic Review - B. F. A. Karim; D. G. Gillam (International Journal of Dentistry)
Objectives. The aim of the present paper was to review the published literature in order to identify all relevant studies for inclusion and to determine whether there was any evidence of the efficacy of strontium and potassium toothpastes in the treatment of dentine hypersensitivity (DH). Methods. Following a review of 94 relevant papers both from searching electronic databases (PUBMED) and hand searching of relevant written journals, 13 studies were identified, and 7 papers (1 for strontium-based toothpastes and 6 for potassium-based toothpastes) were finally accepted for inclusion. The main outcome measures were the methodology and assessment used by Investigators in studies designed to evaluate DH. Results. The results of the present paper would indicate that the reported efficacy of both strontium- and potassium-based toothpastes in relieving DH is questionable. Conclusions. The results from the present paper would appear to support the conclusions of previous investigators that there is only minimal evidence for the efficacy of both strontium- and potassium-based toothpastes in relieving symptoms of DH.